Rancang Bangun Pendeteksi Gelombang Berdiri pada Kabel Koaksial Menggunakan Dioda Detector 1N4148 - Anisa Yulia Haryanti; M. Nanak Zakaria; Aad Hariyadi (Jurnal Jaringan Telekomunikasi, 2021)
In the coaxial transmission line, there is a theory of standing waves. Standing waves occur due to interference between one wave with another wave. Some institutions or colleges may not all have the equipment to observe the exact waveform of an electrical signal or commonly called an oscilloscope. One of them is Malang State Polytechnic. Therefore, in this study I want to make it easier for students, especially in the transmission line practicum course, to be able to describe the standing wave curve in coaxial cable. The results of the system implementation are carried out using an IC LED VU Display as a standing wave curve display where the generator functions as a signal input which regulates the predetermined input frequency and voltage. The results of the test of this system are that standing waves in mismatch conditions (Rl<50?) at points 4/10 to 7/10 , in mismatch conditions (Rl>50?) at points 7/10 and 8/10 are obtained by starting wave condition in match condition there is no reflected wave.